FGF7 secreted from dermal papillae cell regulates the proliferation and differentiation of hair follicle stem cell - Niu Wang; Weidong Zhang; Zhenyu Zhong; Xiongbo Zhou; Xinran Shi; Xin Wang (Journal of Integrative Agriculture)
Hair follicle stem cell (HFSC), capable of self-renewal and differentiation in hair follicle, represents an emerging stem cell model for regenerative medicine. The interaction between HFSC and dermal papilla cell (DPC) governs hair follicle development. FGF7 functions as a paracrine protein regulating epithelial proliferation, differentiation and migration. The single-cell transcriptome profiling and immunofluorescence analysis demonstrated that FGF7 localizes at DPC, while FGF7 receptor (FGFR2) expresses in both DPC and HFSC. Through co-culture experiments of HFSC and DPC, the results indicated that FGF7 secreted from DPC promotes the proliferation of DPC and HFSC via Wnt signaling pathway and induces HFSC differentiation. Furthermore, CUT&Tag assay revealed genomic colocalization between FGF7 and pluripotency-related genes and GSK3β. Electrophoretic mobility shift assay (EMSA) demonstrated that FGF7 interacts with the promoter region of CISH and PRKX. This research provides valuable insights into the molecular mechanisms underlying the hair cycle. Understanding the interaction between HFSC and DPC, as well as the role of FGF7, may advance regenerative medicine and hair loss treatment.